2012
DOI: 10.1093/cvr/cvs161
|View full text |Cite
|
Sign up to set email alerts
|

Bradykinin restores left ventricular function, sarcomeric protein phosphorylation, and e/nNOS levels in dogs with Duchenne muscular dystrophy cardiomyopathy

Abstract: Cardiomyopathy in GRMD dogs is characterized by profound LV subendocardial dysfunction, abnormal sarcomeric protein phosphorylation, and impaired e/nNOS, which can be normalized by bradykinin treatment. These data provide new insights into the pathophysiological mechanisms accounting for DMD cardiomyopathy and open new therapeutic perspectives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
32
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 53 publications
5
32
0
Order By: Relevance
“…In contrast to skeletal muscle where the RyR nitrosation in dystrophy closely follows the muscle inflammation and up-regulation of iNOS, the cellular pathway leading to hyper-S-nitrosation of RyRs in cardiac dystrophy are yet to be elucidated. This scenario may be quite complex as the levels of SR bound NOS1 and caveolae-associated endothelial NOS (eNOS, NOS3) are reduced in hearts of dystrophic mice and dogs [19,70] while the levels of inflammatory-induced NOS2 are increased only in adult (180 days old) mdx mice [53]. It is conceivable that oxidative stress and extensive ROS production by NOX are driving forces for RyR S-nitrosation via overproduction of peroxynitrite, at least in early stages of the cardiomyopathy.…”
Section: Cellular Mechanisms Of Cardiac Dystrophymentioning
confidence: 99%
“…In contrast to skeletal muscle where the RyR nitrosation in dystrophy closely follows the muscle inflammation and up-regulation of iNOS, the cellular pathway leading to hyper-S-nitrosation of RyRs in cardiac dystrophy are yet to be elucidated. This scenario may be quite complex as the levels of SR bound NOS1 and caveolae-associated endothelial NOS (eNOS, NOS3) are reduced in hearts of dystrophic mice and dogs [19,70] while the levels of inflammatory-induced NOS2 are increased only in adult (180 days old) mdx mice [53]. It is conceivable that oxidative stress and extensive ROS production by NOX are driving forces for RyR S-nitrosation via overproduction of peroxynitrite, at least in early stages of the cardiomyopathy.…”
Section: Cellular Mechanisms Of Cardiac Dystrophymentioning
confidence: 99%
“…Our previous report showed that GRMD dogs with heart failure display marked alterations in contractile properties as assessed from myocytes isolated from the ENDO layer. These alterations were correlated with abnormal sarcomeric protein phosphorylation and impaired e/nNOS content 3 . In the present work, we investigated the effect of muscular dystrophy on sarcomere structure and its impact on contractile function.…”
Section: Introductionmentioning
confidence: 92%
“…Myofilament Ca 2+ sensitivity and cross-bridge cycling kinetics as indexed by the exponential rate of tension redevelopment (ktr) were measured in single permeabilized cardiomyocytes isolated from frozen dog LV myocardium as previously described 3,6 . The Force-calcium relationship was studied at either 1.9 or 2.3 µm sarcomere length (SL) 8 .…”
Section: Permeabilized Cardiomyocyte Mechanicsmentioning
confidence: 99%
“…Unfortunately, long-term intravenous administration of NBD was found to induce untoward infusion reactions even in normal dogs. In addition to anti-inflammatory drugs, CXMD dogs have also been used to test calpain inhibitor (172), proteasome inhibitor (173), bradykinin (174,175), and laminin-111 protein therapy (176). Proteasome inhibitor reduced muscle inflammation and partially restored dystrophin-associated glycoprotein complex.…”
Section: Therapeutic Testing In the Canine Model And Impact On Patienmentioning
confidence: 99%